Accounting for test reliability in student progression: the reliable change index. Issue 7 (July 2016) - Zahra, Daniel; Hedge, Craig; Pesola, Francesca; Burr, Steven
Abstract : Context: Developed by Jacobson and Truax, the reliable change index (RCI) provides a measure of whether the change in an individual's score over time is within or beyond that which might be accounted for by measurement variability. In combination with measures of whether an individual's final score is closer to those of one population or another, this provides useful individual‐level information that can be used to supplement traditional analyses. Objectives: This article aims to highlight the potential of the RCI for use within medical education, particularly as a novel means of monitoring progress at the student level across successive test occasions or academic years. Methods: We provide an example of how the RCI can be applied informatively to assessment evaluation, and discuss its wider usage. Conclusions: The RCI approach can be used to identify and support failing students, as well as to determine best teaching and learning practices by identifying high‐performing students. Furthermore, the individual‐level nature of the RCI makes it well suited for educational research with small cohorts, as well as for tracking individual profiles within a larger cohort or addressing questions about individual performance that may be unanswerable at group level. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss